Characterization of geological and lithological features in the area proximal to tritium-contaminated groundwater at the Semipalatinsk test site. - Medet Aktayev; Sergey Subbotin; Assan Aidarkhanov; Almira Aidarkhanova; Lyubov Timonova; Natalya Larionova (PLoS ONE, 2024)
The article presents the results of a study of groundwater contaminated with tritium in the vicinity of the 'Atomic Lake' - a crater filled with water as a result of a thermonuclear explosion on the territory of the former Semipalatinsk test site. This crater was created as part of an experimental thermonuclear explosion in 1965 with the aim of creating an artificial reservoir in arid areas. The study was carried out to identify the source of groundwater contamination near the crater formed from a thermonuclear test. There were two possible factors of pollution: the influence of contaminated water from the crater on the groundwater of the adjacent area, or groundwater polluting the water in the crater. It was necessary to find out the source of groundwater contamination and its connection with the water in the funnel. For this purpose, a study of the geological and lithological conditions of the territory adjacent to the funnel was carried out, which was carried out using drilling operations and hydrological measurements. Drilling work made it possible to study the depth of distribution of groundwater, hydrological work made it possible to determine the conditions of distribution of groundwater, as well as to take samples of groundwater. The assessment of the degree of groundwater contamination was carried out through water sampling and laboratory analysis. As a result, it was established that the geological and lithological conditions of the area limit the flow of contaminated groundwater to the water in the crater - the 'Atomic Lake'. Despite the fact that the waters in the crater from a thermonuclear explosion and the groundwater of the adjacent territory are contaminated with the radionuclide tritium, they have different sources of contamination and are not interconnected. Radionuclide analysis of groundwater showed that increased concentrations of tritium with a specific activity of up to 95 000 Bq/l are found in groundwater near the river bed. Shagan and this is due to the influence of the flow of groundwater coming from other parts of the landfill.